On Poincare duality for pairs (G,W) - Carreira Andrade, Maria Gorete [UNESP]; Campello Fanti, Ermnia de Lourdes [UNESP]; Femina, Ligia Lais (De Gruyter Open Ltd, 2015)
Let G be a group and W a G-set. In this work we prove a result that describes geometrically, for a Poincare duality pair (G, W), the set of representatives for the G-orbits in W and the family of isotropy subgroups. We also prove, through a cohomological invariant, a necessary condition for a pair (G, W) to be a Poincare duality pair when W is infinite.
Keywords: Poincare duality pairs; Cohomology of groups; Cohomological invariants